Performance evaluation of HMA using recycled brick powder as filler with Superpave aggregate gradation - Tamiru Habte; Getachew Kebede; Agon Elmer; Anteneh Geremew (Advances in Civil and Architectural Engineering)
The performance of hot-mix asphalt (HMA) typically hinges on the quality of the ingredients utilized in blending the asphalt concrete. In this study the Superpave mix design method is used to investigate the performance of HMA with recycled brick powder (RBP) added as a filler. A non-probability sampling technique was used to gather samples. The engineering characteristics of materials used in HMA components, such as bitumen (80/100 penetration grade), aggregates, RBP, and crushed stone dust (CSD), were verified against standard specifications. The impact of RBP as a filler substance on the Marshall properties, stripping tests, moisture susceptibility, and permanent deformation in asphalt mixtures were assessed. Chemical analysis of the RBP indicated that silicon dioxide, aluminium oxide, and iron oxide collectively constituted 62,68; 14,74 and 9,16 %, respectively, of its composition satisfying the minimum requirements for natural pozzolan materials. The RBP specific gravity and plastic index, were 2,66 and non-plastic, respectively. HMA specimens were prepared with conventional filler CSD in three proportions (4, 5, and 6 %) and eight bitumen contents from (3,0-6,5 %) with 5,0 % of CSD selected as the control mix. The CSD filler in proportions of 4, 3, 2, 1, and 0 % was combined with RBP in proportions of 1, 2, 3, 4, and 5 %, respectively, to replace the 5 % CSD control mix. The optimum bitumen content was maintained at 5,45 %. The replacement rates of 3 % RBP + 2 % CSD meet ERA standard specifications for Marshall properties, offering a cost-effective solution with low permanent deformation (2,88 mm) and high tensile strength ratio (94,39 %). Incorporating RBP in HMA aligns with the criteria suggested in the Superpave aggregate gradation for up to 3 % RBP + 2 % CSD replacement of conventional filler in HMA production.